Anal Fissure in Children - Patkova, Barbora; Wester, Tomas (European Journal of Pediatric Surgery, 2020)
Anal fissure is a common clinical problem in children and is defined as a longitudinal tear in the anal canal. The typical presentation is painful defecation and rectal bleeding. The etiology of anal fissure is unknown, but passage of hard stools and increased internal anal sphincter pressure are considered important factors. The treatment is oriented to relieve the spasm of the internal anal sphincter, which prevents healing of the fissure. Conservative management with stool softeners, topical analgesics, and sitz baths is recommended as first-choice therapy. Surgical treatment has been replaced by nonoperative management as definitive therapy, which is associated with a marginally higher success rate than placebo. Most recent studies have focused on nonoperative treatment with glyceryl trinitrate, calcium channel blockers, or botulinum toxin injection treatment. There are a few controlled studies to compare the different nonoperative treatment options in children. Success rates vary between the studies, and there is no clear evidence about which is the optimal nonoperative treatment. A significant recurrence rate has been reported after nonoperative management of anal fissure. It is important to treat constipation to avoid recurrent tears in the anal canal.
Keywords: anal fissure; children; glyceryl trinitrate; diltiazem; botulinum toxin